SOCIAL MEDIA INFLUENCERS AS DIGITAL MARKETING CATALYSTS: MEASURING ROI AND BRAND ENGAGEMENT - Henny Noviany; Yusnaini; Abdul Wahab Syakhrani (CV. Adiba Aisha Amira, 2024)
In the growing digital era, influencers have become a critical component in many brands' marketing strategies. The research method used was a literature review. The results show that influencer marketing can increase digital marketing ROI when implemented with the right strategy. However, its effectiveness is highly dependent on the fit between the influencer and the brand, the quality of the content, and the engagement strategy used. Hence, the importance of a holistic approach in measuring the success of influencer campaigns, which not only focuses on short-term metrics but also considers the long-term impact on brand perception and loyalty.